2019
DOI: 10.1007/s12328-019-01055-w
|View full text |Cite
|
Sign up to set email alerts
|

Pill-induced esophagitis caused by ingesting excessive caffeine tablets

Abstract: A 19-year-old woman with suicidal thoughts consumed 24 anhydrous caffeine tablets and was admitted to our hospital. After being discharged from the hospital, her oral intake remained impaired because of retrosternal pain and she was readmitted. An upper gastrointestinal endoscopy revealed diffuse ulcers throughout the mid-to-lower esophagus; the patient was diagnosed with caffeine-induced esophagitis. She recovered soon after conservative treatment. A follow-up endoscopy performed 1 month after the patient was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Here, we have presented a very rare case of severe erosive esophagitis due to caffeine overdose. To the best of our knowledge, only one case of esophageal injury secondary to an overdose of caffeine tablets has been reported in the English literature; three other cases of esophageal injury secondary to caffeine overdose have been reported in Japanese [ 6 ]. Miyata et al reported the case of a 19-year-old female who developed diffuse lower esophageal ulcers without any gastric ulcers or erosions following the consumption of 24 tablets of Estaron-mocha (SSP Co. Ltd., Chuo-Ku, Japan) amounting to 2.4 g of caffeine in an apparent suicide attempt [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, we have presented a very rare case of severe erosive esophagitis due to caffeine overdose. To the best of our knowledge, only one case of esophageal injury secondary to an overdose of caffeine tablets has been reported in the English literature; three other cases of esophageal injury secondary to caffeine overdose have been reported in Japanese [ 6 ]. Miyata et al reported the case of a 19-year-old female who developed diffuse lower esophageal ulcers without any gastric ulcers or erosions following the consumption of 24 tablets of Estaron-mocha (SSP Co. Ltd., Chuo-Ku, Japan) amounting to 2.4 g of caffeine in an apparent suicide attempt [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, theophylline, a metabolite of caffeine, is known to induce gastroesophageal reflux when it is dissolved in the GI tract. Because both caffeine and theophylline are structurally and toxicologically similar, caffeine likely shares a similar mechanism of esophageal injury to theophylline [ 3 , 6 ]. Patient-related factors of pill-induced esophagitis, such as ingestion of pills with an inadequate volume of water, may also play a role in the GI toxicity of caffeine [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But in humans, excessive amounts of caffeine (>2000 ​mg) can give rise to significant toxic effects, including tachycardia, severe hypertension, arrhythmia, seizures, nausea, vomiting, and even death. However, individuals sensitive to caffeine can exhibit adverse effects at lower doses ( Miyata et al., 2020 ; Duncanson et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%